Thorn Bug, Umbonia crassicornis (Amyot and Serville) (Insecta: Hemiptera: Membracidae): EENY175/IN332, rev. 8/2004 - Mead, Frank W. (EDIS, 2021)
Revised! This document is EENY-175 (originally published as DPI Entomology Circular 8), part of the Featured Creatures collection. Published by the Entomology and Nematology Department, UF/IFAS Extension, August 2004. EENY175/IN332: Thorn Bug, Umbonia crassicornis (Amyot and Serville) (Insecta: Hemiptera: Membracidae) (ufl.edu)